Melalui Pendekatan Saintifik Model Pembelajaran Covid-19 untuk Meningkatkan Hasil Belajar Peserta Didik pada Mata Pelajaran Bahasa Indonesia Marteri Teks Pidato Persuasif Metode Luring di Kelas IX. 8 SMP Negeri 1 Payakumbuh Semester Ganjil Tahun Pelajaran - Yulianis Yulianis (Departement of Mathematics Education, 2022)
This study aims to see and analyze the improvement of Indonesian language learning outcomes for persuasive speech texts in class IX. 8 SMP Negeri 1 Payakumbuh, West Sumatra. This research was carried out using the Classroom Action Research method which consisted of two cycles, in each cycle consisting of; planning, action, reflection, and evaluation. It is carried out from August to November 2021. The data is processed in each cycle and then analyzed using percentages. The results obtained in the pre-cycle, cycle I and cycle II showed an increase. The value of students' knowledge increased from 74 in the pre-cycle to 81 in the first cycle and to 95 in the second cycle. The skill value also increased from 74 in the pre-cycle to 91 in the first cycle, and to 96 in the second cycle. The percentage of students' acquisition of knowledge scores increased from 35% in the pre-cycle to 79% in the first cycle to 86% in the second cycle. Meanwhile, the percentage of skill scores also increased from 38% in the pre-cycle to 86% in the first cycle to 93% in the second cycle. On the other hand, students who did not complete the percentage decreased. Based on the results of the second cycle of assessment, it can be interpreted that the implementation of the Offline Covid-19 Learning Model is quite effective in learning Indonesian. The implication obtained from this research is that the use of a scientific approach to the Covid-19 Offline Learning model can improve student learning outcomes.